LESI LIKENOID ORAL YANG BERHUBUNGAN DENGAN RESTORASI AMALGAM DAN PERAWATANNYA: ORAL LICHENOID LESION RELATED TO AMALGAM RESTORATION AND ITS TREATMENT - Sayuti Hasibuan (Dentika: Dental Journal, 2010)
The oral lichenoid reaction is to be regarded as a reaction pattern within the oral mucous directed towards a specific agents in patients predisposed to develop such a reaction. During the last decade, it has been discussed that dental amalgam plays etiological role in the development of lichenoid reaction in oral mucous. Removal of amalgam fillings has led to healing or clinical improvement of a majority of existing lichenoid lesions. We reported a case of oral lichenoid reaction associated to amalgam restoration. A 53 years old woman presented with a sore mouth and ulceration affecting the gingival and buccal mucous in the region of maxillary right first molar filled with amalgam. Patient had no medical history and medication. After replacing amalgam restoration with resin composite and applied of topical corticosteroid, the lesion clinically disappeared. In conclusion, this case suggested that replacement of amalgam restoration with the other material and applied topically steroid be effective in the resolution of the oral lichenoid lesion related to amalgam restoration.